Enhancing the water splitting performance via decorating Fe2O3 nanoarrays with oxygen-vacancy-rich Ni1-xFexS electrocatalyst. (January 2021) - Wei, Y.; Liao, A.; Zhou, Y.; Zou, Z.
Abstract: In this work, oxygen-vacancy-rich Ni1-x Fex S electrocatalyst modified Fe2 O3 nanoarrays photoanode (denoted as Ni1-x Fex S/Fe2 O3 ) has been prepared firstly through a facile dripping solution method and a sulfurized process. As-prepared Ni1-x Fex S/Fe2 O3 anode shows a very high photocurrent density of ∼3.48 mA/cm 2 at 1.23 V vs. reversible hydrogen electrode (RHE) and a saturated photocurrent density of 7.03 mA/cm 2 at 1.57 V vs. RHE in PEC water splitting, which is 2.5 times of Fe2 O3 (1.38 mA/cm 2 at 1.23 V vs. RHE and 2.98 mA/cm 2 at 1.57 V vs. RHE, respectively). Moreover, the photocurrent onset potential shows a distinct negative shift of about 272 mV. The Ni1-x Fex S/Fe2 O3 photoanode is controllable to achieve superior PEC performance because of the synergistic effects of Ni1-x Fex S electrocatalyst and oxygen vacancies. Since in situ formed Ni1-x Fex S electrocatalyst not only increase electrochemical active surface area of electrode, but also dramatically decrease solid and electrolyte interface resistance as well as dramatically suppresses charge carrier recombination in Fe2 O3 photoanodes. In the meanwhile, introduced the oxygen vacancies in a sulfurized process of Ni1-x Fex S electrocatalyst serve as active sites for sufficient chemical reaction. Hence, our work testifies oxygen-vacancy-rich Ni1-x Fex S not only act as a promising OER electrocatalyst, but also offers a new strategy to prepare efficient and low-cost PEC solar energy conversion devices. Graphical abstract: Image 1 Highlights: The oxygen-vacancy-rich Ni1-x Fex S/Fe2 O3 photoanode is manufactured for the first time by a facile process. The photoanode exhibits an ultrahigh photocurrent density. The photoanode presents an obvious cathodic shift of onset potential relative to Fe2 O3 . In situ formed Ni1-x Fex S electrocatalyst and introduced oxygen-vacancy facilitate charge separation and transfer.